Projeto e orçamento em obras de pequeno porte: estudo de caso na obra cama e cadeia - Pereira Júnior, Carlos (Universidade Federal Rural do Semi-Árido, 2017)
The present work deals with the management of projects in the context of the municipalities of the high west potiguar, state Rio Grande do Norte, for this the research takes as object of analysis the public work Camera and Chain built in the municipality of Portalegre, in search of evaluating and identify the main problems or obstacles to carry out this work within the deadlines riginally established. The study is based on bibliographical research, taking an approach on the subject of planning and project management in the public sector, as well as in studies and researches elaborated. With the accomplishment of the research, it was found that the lack of planning, of compatibility between the projects elaborated and the reality in loco, mainly the project management, contributed for the delay in the construction of the mentioned work within the delimited period. In this way, the research showed that, in addition to the bureaucracy related to contraction, there is a dependence between three antagonistic agents, the designer, the city hall and the constructor, being management in the public sphere, aligned with the interest of these three agents , thus making it difficult to concretize works efficiently.
Monografia
Keywords: Gestão de projeto; câmara e cadeia; Portalegre e planejamento; project management; chamber and chain; Portalegre and planning; ENGENHARIAS::ENGENHARIA CIVIL